Organizational (Re-)Configurations of Introducing Medical Innovations into Sustainable Practice: The Case of TAVI - Jasmina MASOVIC; Emil VARGOVIC; Bojan MORIC MILOVANOVIC (Communications of International Proceedings, 2024)
This study explores the adoption of Transcatheter Aortic Valve Implantation (TAVI) at a Norwegian university hospital, with an emphasis on the organizational and relational dynamics required to sustain new medical innovations in long-term practice. The article highlights a lack of empirical studies on the early-phase relational configurations and negotiations necessary for sustaining new procedures in healthcare. Employing a five-year ethnographic case study approach, we gathered data through direct observations and semi-structured interviews involving multiple stakeholders, including medical practitioners, managers, technology vendors, and many others. Our findings reveal that sustaining TAVI as a standard practice required establishing relational configuration among multidisciplinary stakeholders, balancing collaborative learning with jurisdictional boundaries. A notable outcome was the division of the TAVI team into sub-groups, facilitating specialization and enhancing procedural efficiency, thus promoting TAVI’s routinization. These findings contribute to a relational framework for understanding how early stakeholder configurations and collaborative patterns affect the sustainability of healthcare innovations.
Keywords: sustainable innovations; healthcare management; new technologies; relational theory; practice-based studies